Research in the Classroom: Introducing Nanomaterials at a Two-Year College - Kim, Jihyun; Roth, Christopher; Zhang, Sheng (International Journal of Research in STEM Education, 2020)
This article illustrates how the authors transformed Ã¢â‚¬Å“research in the classroomÃ¢â‚¬Â into chemistry courses at a two-year college in the form of short course-based research experience. The students worked in groups to research nanomaterials, came up with a series of carbon nanoparticles precursors from waste materials, and developed simple and cost-effective methods to produce carbon nanoparticles. Not surprisingly, students became more active learners as they were in charge of learning, and were given authority to modify lab activities with their learning experience progressing. A deeper approach to learning helped students better appreciate chemical sciences, increase conceptual learning, and become responsible citizens. The project also provided a platform to discuss sustainability, green chemistry, and nanomaterials. To increase the efforts for student success, academic technologies were utilized to aid the project.